The rough guide to Memphis blues : reborn and remastered [compact disc]. - Batts, Will; Burse, Charlie; Cannon, Gus, 1883-1979; Davenport, Jed; Dickson, Pearl; Dickson, Tom (Vocalist); Estes, Sleepy John, 1899-1977; Hart, Hattie; Kelly, Jack, -1960; Lewis, Furry, 1893-1981; Lewis, Noah, 1895-1961; Memphis Minnie, 1897-1973; et al. (Music rough guide., 2022)
From the classic sounds of the jug band heyday to the earthy blues straight from the Mississippi Delta, Memphis was at the very epicentre of the 1920s country blues explosion. This Rough Guide charts the city's huge influence with classic tracks by blues legends Memphis Minnie, Furry Lewis, Sleepy John Estes and many more.